The genus Indonemoura Baumann, 1975 (Plecoptera: Nemouridae) from China - Li, Weihai; Yang, Ding (Zootaxa, 2006)
The species of the genus Indonemoura from China are reviewed. The following three species are described as new to science: Indonemoura baishanzuensis n. sp., Indonemoura guangdongensis n. sp. and Indonemoura yangi n. sp. A key to the species of the genus from China is given. The distribution of Indonemoura in China is discussed.